Leachate treatment using up-flow anaerobic sludge blanket system - Ridzuan, Mohd Baharudin; Daud, Zawawi; Ahmad, Zulkifli; Abd Latiff, Ab Aziz; Awang, Halizah (Penerbit UTHM, 2018)
Leachate is one of the major problems to overcome in managing the landfill. Low cost treatment, less maintenance and environmental friendly are the target on how to treat the leachate. This research focused on the effectiveness of Up-flow Anaerobic Sludge Blanket on leachate treatment. This study was carried out upon treatment of leachate by using Up-flow Anaerobic Sludge Blanket through reactor tank in lab-scale. Without a proper treatment, leachate will give a negative effect to the environment and become pollutant. This research is determining percentage nutrient removal on leachate. The leachate characteristic also been investigated. The main parameters evaluations are Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Total Nitrogen (TN) and Total Phosphorus (TP). Experiments were run in duration of 30 days were sample for test had been taken each 3 days. Results show that the capability of UASB in the removal several parameters. This UASB had a greater ability in removal of Total Phosphorus and TSS with 89% and 81% respectively. For COD, BOD and TN, the values are 74%, 64% and 50%. Based on these results, it clearly shows that UASB capable to remove physical and chemical properties of leachate.